A Case History Studying On Displacement Controlling In Deep Excavation - Feng Yongxuan (Deep Foundations Institute, 1991)
Anchored sheep pile is normally used in deep excavations, many of which only require stability in accordance with Terzaghi theory. In this paper, based on the experience, new lateral earth pressure method is adopted taking account into interaction among soil, anchors and sheet piles so that a group for the project under very difficult conditions and very severe requirments, especially, for the displacements are determined according to that mentioned above. During and after construction, displacements monitoring were carried out for about four months, which was proved that there was a little difference between calculation and practice.